Performa Produksi dan Analisis Kelayakan Usaha Penggemukan Domba yang Disuplementasi Probiotik Bioplus di Desa Kaso Kecamatan Tambaksari - Lilis Riyanti; Mutia Sari; Kenedy Putra (Politeknik Negeri Jember, 2022)
Supplementation of Bioplus probiotic is the feeding strategy that can be applied to optimize sheep production in Kaso Village, Tambaksari District, Ciamis. Bioplus contains rumen microorganism that play a role in rumen digestion process. The aim of the study were to analyze the supplementation of Bioplus probiotic on production performance of sheep and to analyze the feasibility of feedlot sheep in Kaso village. The treatment consist of two treatment P0 = control and P1 = control + rice brand + Bioplus probiotic 1 doze (150 g). The variable measured such us average daily gain, dry matter (DM) intake, ration efficiency, income over feed cost (IOFC). The Feasibility variable measured such us R/C ratio, B/C ratio, BEP price and BEP production. The Data were analyzed using independence t-test and descriptive analysis for feasibility variables. The results of the study showed that there was an effect on average daily gain, ration efficiency and IOFC (P<0,05) but did not effect on DM intake (P>0.05). The results of the feasibility analysis show that there is an increase in income, the B/C ratio increases with the addition of probiotics and the R/C ratio P1 is higher and most feasible. Price BEP and production BEP P1 are better than P0. Thus, the supplementation of Bioplus probiotic was able to increase the production performance and income of sheep farmers in Kaso Village.